2009
DOI: 10.1007/s12640-009-9144-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Tityus bahiensis Scorpion Venom on Tetrodotoxin-Sensitive and Tetrodotoxin-Resistant Sodium Currents

Abstract: We examined modification of sodium channel gating by Tityus bahiensis scorpion venom (TbScV), and compared effects on native tetrodotoxin-sensitive and tetrodotoxin-resistant sodium currents from rat dorsal root ganglion neurons and cardiac myocytes. In neurons, TbScV dramatically reduced the rate of sodium current inactivation, increased current amplitude, and caused a negative shift in the voltage-dependence of activation and inactivation of tetrodotoxin-sensitive channels. Enhanced activation of modified so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…After incubating with T. bahiensis venom, the activation and the current–voltage curves were shifted to more negative potentials (to the left) and the current-peak amplitude increased. Similar results were reported with T. bahiensis venom using sensory dorsal root ganglia (DRG) neurons and ventricular cardiomyocytes (Moraes et al 2011 ). T. bahiensis venom also markedly reduced the rate of Na v -current inactivation in these cells (Moraes et al 2011 ).…”
Section: Discussionsupporting
confidence: 86%
“…After incubating with T. bahiensis venom, the activation and the current–voltage curves were shifted to more negative potentials (to the left) and the current-peak amplitude increased. Similar results were reported with T. bahiensis venom using sensory dorsal root ganglia (DRG) neurons and ventricular cardiomyocytes (Moraes et al 2011 ). T. bahiensis venom also markedly reduced the rate of Na v -current inactivation in these cells (Moraes et al 2011 ).…”
Section: Discussionsupporting
confidence: 86%
“…Isolation and cell culture of rat DRG neurons DRG neurons were obtained from the lumbar segments of 10 to 14-w old male Wistar rats (220-250 g body weight) using an enzymatic dissociation procedure as described previously (Joca et al, 2012;Moraes et al, 2011). Rats were rendered unconscious by exposure to CO 2 and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…AmmVIII and AaH1 were found not to alter the Nav1.9 current in DRG neurons (Abbas et al, 2013). Recent publications have suggested that Tityus bahiensis scorpion venom (TbScV) (Moraes et al, 2011) and TsVII (Tityus serrulatus) (Gilchrist and Bosmans, 2012) have potential action on Nav1.8 and Nav1.9 channels, although this requires further assessment and characterization.…”
Section: Scorpion Venom Peptide Actions On Voltage-gated Sodium Channelsmentioning
confidence: 93%